Vascular and Neural Changes During Body Inversion: Preliminary Findings - Lovasik, J.V; Kothe, A.C; Spafford, M.M (Canadian Journal of Optometry, 2021)
This report examines the influence of gravity on physiological fluid pressures within the body. The interest in the influence of gravity on ocular structures and function is topical not only because of the current fashion of body inversion devices as forms of exercise, but also the ocular consequence of a cephalic redistribution of blood with its subsequent effect on IOP during the micro-gravity environment of spaceflight. For the ophthalmic practitioner, the effect of body orientation on intraocular pressure and on the blood supply to the eye is of practical importance. In this paper the influence of precisely controlled body positions on the intraocular pressure, central retinal artery pressure, and systemic blood pressure is presented. Deficits in visual neural function resulting from body inversion are documented. Clinical implications of these findings are discussed.